PENGARUH MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) BERBANTU VIDEO ANIMASI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 05 PULAU PUNJUNG - Ratnawati; Dwi Novri Asmara; Rita Sartika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low mathematics learning outcomes of third-grade students at SDN 05 Pulau Punjung in multiplication, caused by a lack of variety in learning models and media. This study aimed to determine the effect of implementing the Student Teams Achievement Division (STAD) learning model with animated videos on students' mathematics learning outcomes. The study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The sample size was 20 students, selected using a saturated sampling technique. Data collection included pretests and posttests, along with documentation. Data analysis was conducted through normality tests and hypothesis testing using SPSS version 20. The results showed an average pretest score of 51.5, increasing to 79.25 on the posttest after implementing the STAD model with animated videos. Normality tests for the pretest and posttest showed a normal distribution. Because all were normally distributed, a parametric hypothesis test was conducted using the paired sample t test SPSS 20. The results of the hypothesis test showed a significance value of 0.000 <0.05, so H₀ was rejected and H₁ was accepted. Thus, it can be concluded that the STAD learning model assisted by animated videos has a significant effect on the mathematics learning outcomes of grade III students of SDN 05 Pulau Punjung.